2017
DOI: 10.15345/iojes.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effects of Problem-Based Learning Activities Supported via Flipped Classroom and LEGO-LOGO Practices on the Success and Motivation of High School Students

Abstract: The purpose of this study was to investigate the effects of algorithm teaching on the academic success and motivations of high school students by using FC Model and LEGO-LOGO practices. In the research, pretest-posttest control group pattern, one of quantitative research methods included in real experimental patterns, was used. Criterion sampling, one of purposeful sampling methods, was used to determine the study group of the research. The study group consisted of 42 students in 3 different classrooms enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…This result can be interpreted as that students who receive robotics assisted programming education are more motivated to course of Program Languages I than students who receive robotics unassisted programming education. This result shows similarities research results of Çukurbaşı & Kıyıcı (2017), Lykke et all., (2014), McWhorter & O'Connor (2009, Nugent et all., (2009) and Piteira & Haddad (2011) in the literature. Martínez Ortiz (2015) was found that LEGO ® Mindstorms practices increase students' motivation to learn.…”
Section: Conclusion and Suggestionssupporting
confidence: 91%
“…This result can be interpreted as that students who receive robotics assisted programming education are more motivated to course of Program Languages I than students who receive robotics unassisted programming education. This result shows similarities research results of Çukurbaşı & Kıyıcı (2017), Lykke et all., (2014), McWhorter & O'Connor (2009, Nugent et all., (2009) and Piteira & Haddad (2011) in the literature. Martínez Ortiz (2015) was found that LEGO ® Mindstorms practices increase students' motivation to learn.…”
Section: Conclusion and Suggestionssupporting
confidence: 91%
“…This section considers how these questions were addressed in the research conducted here. Firstly, we explored whether this type of LOGO coding has an influence on the learning of problem-solving in mathematics, especially in geometric construction, and it was found, in line with the literature (Çukurbaşı & Kıyıcı 2017), this approach embracing PBL for SDL has a positive influence on the learning. Furthermore, we probed how problem-solving skills in geometry can be developed using the LOGO coding environment, and it was evident that using this PBL for SDL approach, these skills were developed and the learner responses confirmed this.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, it has been found that LOGO provides an apt environment for PBL. In this regard, Çukurbaşı and Kıyıcı (2017) found that PBL activities could be facilitated through LOGO and that this contributed positively not only to student success but also motivation in the learning context especially if this is combined with a flipped-classroom approach. This aligns well with other research on PBL in mathematics contexts, where it was determined that such an approach motivated students when they collaborated in problem-solving activities (Botty et al 2016).…”
Section: Coding By Logo: Learning In a Fun Way And Initiating Computa...mentioning
confidence: 99%
“…When the literature is examined, there are investigations of the effectiveness of the FLM in software, mathematics, physics, chemistry, health care, statistics, engineering and many other fields (Behmanesh et al, 2020 ; DeSantis et al, 2015 ; Fernández-Martíne et al, 2020 ; Ghanaat & Habibzadeh, 2021 ; Gannod et al, 2008 ; Huang et al, 2020 ; Jdaitawi, 2020 ; Kettle, 2013 ; Kong, 2015 ; Lestari, 2021 ; Mason et al, 2013 ; McLaughlin et al, 2014 ; Pierce & Fox, 2012 ; Talbert, 2014 ; Touchton, 2015 ; Webb & Doman, 2020 ; Yestrebsky, 2015 ). Moreover, it is seen that studies examining the effects of the FLM on many variables such as academic achievement (Hwang et al, 2021 ; Pierce & Fox, 2012 ), attitude (Chao et al, 2015 ; Güç, 2017 ; Sağlam, 2016 ; Webb & Doman, 2020 ), motivation (Çukurcubaşı, 2016 ; Halili et al, 2021 ), mental risk taking (Çakır & Yaman, 2018 ), and reading level (Cashin, 2016 ) are increasing in the literature. The literature review indicates that the use of the flipped learning model (FLM) in learning environments has increased in recent years.…”
Section: Review Literaturementioning
confidence: 99%